Efek Tayangan Indo Beauty Vlogger di Situs Youtube Terhadap Perilaku Imitasi Mahasiswi - Anisa Lestari; Fatmawati Fatmawati (LPPM Institut Nasional Laa Roiba Bogor, 2021)
Beauty Vlog is one content that is being watched by many Indonesian women on the YouTube site. From year to year the number of Beauty Vloggers from Indonesia is increasing, even giving birth to a community called Indo Beauty Vlogger with viewers who have reached 300 million views. This study aims to determine how the effect of the Indo Beauty Vlogger show on imitation behavior and how big the effect is among KPI female students of UIN Syarif Hidayatullah Jakarta. This study uses a positivistic or classical paradigm with a quantitative approach. The method used is a survey method. The sampling technique used in this study was purposive sampling with 172 respondents. The theory used is Albert Bandura's Social Learning Theory. The results of this study are Ha accepted, which means that cognitive, affective, and behavioral effects can influence imitation behavior among female students. Partially, cognitive, affective, and behavioral effects have a significant influence on student imitation behavior. Then by looking at the R Square value of 0.606 which means that cognitive effects, affective effects, and behavioral effects affect the imitation behavior of female students by 60%. Meanwhile, the remaining 40% is influenced by other variables outside the model used in this study.